2021
DOI: 10.3389/fcell.2021.714787
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA Activated by DNA Damage: Review of Its Roles in the Carcinogenesis

Abstract: Long intergenic non-coding RNA 00657 (LINC00657) or “non-coding RNA activated by DNA damage” (NORAD) is an extremely conserved and copious long non-coding RNA (lncRNA). This transcript has pivotal role in the preservation of genome integrity. Several researches have appraised the role of NORAD in the evolution of human cancers with most of them indicating an oncogenic role for this lncRNA. Several miRNAs such as miR-199a-3p, miR-608, miR−155−5p, miR-590-3p, miR-495-3p, miR-608, miR-202-5p, miR-125a-3p, miR-144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…reported that miR-155-5p had been recognized as a target of non-coding RNA activated by DNA damage in different cell lines. Furthermore, non-coding RNA activated by DNA damage also interacted with the Akt/mTOR pathway [ 51 ]. In nephroblastoma, miR-155-5p targeted IGF2 directly to inactivate the PI3K/AKT/mTOR pathway and exert tumor suppressor effects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that miR-155-5p had been recognized as a target of non-coding RNA activated by DNA damage in different cell lines. Furthermore, non-coding RNA activated by DNA damage also interacted with the Akt/mTOR pathway [ 51 ]. In nephroblastoma, miR-155-5p targeted IGF2 directly to inactivate the PI3K/AKT/mTOR pathway and exert tumor suppressor effects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 30 ) indicated that HOXD-AS1 combines with miR-608 and increases frizzled class receptor 4 (FZD4), participating in the development of ovarian cancer. The lncRNA NORAD has also been found to bind to miR-608 in cancer and upregulate forkhead box O6 (FOXO6) in gastric cancer, accelerating cell growth ( 19 , 44 ). A similar axis also exists in ovarian cancer, but surprisingly, NORAD induces overexpression of signal transducer and activator of transcription 3 (STAT3) by interacting with miR-608 and functions as a tumor suppressor ( 31 ).…”
Section: Regulation Of Mir-608 Expressionmentioning
confidence: 99%
“…Long intergenic non-coding RNA 00657 (LINC00657) or otherwise called “NORAD” (non-coding RNA activated by DNA damage) has crucial effect on preserving genome stability and progression of cell cycle, therefore its dysregulation leads to cancer [ 12 ]. Up-regulation of LINC00657 has been reported in various tumors and was considered an indicator of poor survival, like breast cancer, gastric cancer, hepatocellular carcinoma, and lung cancer [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%